Long-term Impact of a Positive Youth Development Program on Dating Violence Outcomes During the Transition to Adulthood - Taussig, Heather ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study identified risk and protective factors for dating violence (DV) among young adults (ages 18-22) with a history of maltreatment and placement in foster care, and who had enrolled in Fostering Healthy Futures (FHF) during 2002-2009. FHF is a Colorado-based positive youth program for maltreated youth. This study focused on factors that ameliorated the effects of risk to reduce DV perpetration and victimization in young adulthood. The participants were interviewed at three different points during the FHF time frame. That data provided a basis for determining risk and mediating factors which in turn were compared to the current study's DV outcomes. The risk and protective factors included: Mental health Substance abuse Social support Gender Stereotypes Attitudes about Teen DV Communication Skills Perpetration and victimization outcomes were then examined in relation to the risk and protective factors. The collection includes 1 SPSS file: NIJ-2013-VA-CX-0002---2nd-revision---5-17-18.sav (215 cases / 2023 variables).